Findings in endovaginal ultrasound in hemorrhage in the first trimester of pregnancy - Sánchez Vaca, Milton Steeven (Universidad Ciencia y Tecnología, 2022)
Vaginal bleeding during the first trimester of pregnancy is an event that can cause concern for its possible causes. Through the use of endovaginal ultrasound, it is possible to obtain valuable information on the causes of obstetric hemorrhages that occur from the embryo implantation phase to the final stages of pregnancy. In this work, the findings found recurrently in pregnant patients up to week 12 are exposed. 205 cases that met the study requirements were included in the work, of which 77 ended in abortions (complete 32, incomplete 25, deferred 20) and 128 were abortion threats, the presence of retroplacental hematomas in the cases was 78, and the remaining 50 cases were due to other causes.